Studi Populasi Kuskus Beruang Sulawesi (Ailurops ursinus) Di Cagar Alam Tangkoko, Sulawesi Utara - Repi, Terri; J. Nangoy, Meis; Onibala, Jane S.I.T. (Jurnal Sains Ternak Tropis, 2025)
Sulawesi bear cuscus (Ailurops ursinus) is an endemic marsupial mammal spread across Sulawesi Island and its surrounding islands. However, this species is listed as an endangered species. This study aims to estimate the population of bear cuscus in the Tangkoko Nature Reserve, North Sulawesi, as one of the cuscus conservation areas. This study was conducted for approximately 1 month (1-28 May 2008), using the strip transect sampling method. Some of the data collected were: number of individuals, meeting time, observation distance, general behavior and height of vegetation used by the cuscus. The results of this study found that the population density of bear cuscus (A. ursinus) in the Tangkoko Nature Reserve with a survey area of 1 km2 was 1.66 individuals/km2, with a total estimated population in a representative habitat area of 31.96 km2 of 53.13 individuals/km2.Kuskus beruang sulawesi (Ailurops ursinus) merupakan mamalia berkantung endemik yang tersebar di Pulau Sulawesi dan pulau-pulau sekitarnya. Meski demikian, spesies ini terdaftar dalam spesies terancam. Penelitian ini bertujuan untuk memperkirakan populasi kuskus beruang di Cagar Alam Tangkoko, Sulawesi Utara, sebagai salah satu kawasan konservasi kuskus. Penelitian ini dilakukan selama kurang lebih 1 bulan (1-28 Mei 2008), menggunakan metode strip transect sampling. Beberapa data yang dikumpulkan yaitu: jumlah individu, waktu pertemuan, jarak pengamatan, perilaku laku umum dan ketinggian vegetasi yang digunakan kuskus. Hasil penelitian ini menemukan bahwa kepadatan populasi kuskus beruang (A. ursinus) di Cagar Alam Tangkoko dengan luas wilayah survei 1 km2 adalah sebanyak 1,66 ekor/km2, dengan total dugaan populasi pada luas perwakilan habitat seluas 31,96 km2 sebanyak 53,13 ekor/km2.